ANALISIS NILAI TAMBAH DAN LABA PADA PENGOLAHAN NANAS (Ananas comosus L.) SEGAR MENJADI DODOL NANAS DI KECAMATAN JALANCAGAK KABUPATEN SUBANG - Wanda Fadhilah; Sulistyo Sidik Purnomo; Suhaeni Suhaeni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Pineapple lunkhead is one of processed pineapple fruit mixed with glutinous rice flour, sugar, coconut milk, and other ingredients. Value added is the added value of a commodity because it undergoes a processing, transportation or storage process in a production. This study aims to: (1) Analyze the business description in the agroindustry of processing fresh pineapple into pineapple lunkhead in Jalancagak District, Subang Regency, (2) Analyze the added value of processing fresh pineapple into pineapple lunkhead in Jalancagak District, Subang Regency, (3) Analyze the profit that can be created from processing fresh pineapple into pineapple lunkhead in Jalancagak District, Subang Regency. The research method used is descriptive quantitative and qualitative research. In this study, the researchers set 10 people as respondents using the saturated sampling method (census). The results showed that: (1) Business description in pineapple dodol agroindustry in Jalancagak District, Subang Regency shows that it is currently quite developed. (2) The added value obtained from processing pineapple into pineapple lunkhead for 5 months is an average of Rp. 20,758/kg with a value added ratio of 55%. So based on these results the added value of pineapple lunkhead is said to be high because it has a ratio of > 40%. (3) Average profit from pineapple dodol agoindustry is Rp. 157.459.379 in a period of 5 months with an r/c ratio of 2.76. Pineapple dodol agro-industry in Jalancagak District, Subang Regency is feasible to cultivate.